2006
DOI: 10.1111/j.1365-2443.2006.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained cell proliferation of renal epithelial cells in mice with inv mutation

Abstract: A tubule system is an important component of the nephron, which is the structural and functional unit of the kidney. Expansion of renal tubules results in renal cysts. Hereditary forms of renal cystic diseases suggest that tubular size is determined genetically. The inv was discovered as a mutant with renal cysts and situs inversus . Inv / inv , inv∆ ∆ ∆ ∆ C::GFP ( inv∆ ∆ ∆ ∆ C) mouse was created by the introduction of the inv gene lacking the C-terminus ( inv∆ ∆ ∆ ∆ C) into inv / inv mice. The mouse develops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…3 Our histologic analysis of the kidneys showed that Sdccag8 gt/gt mice displayed a classic nephronophthisis phenotype at P100, with the cystic dilations originating from the DCTs and CCDs. Compared with other mouse models of nephronophthisis, [22][23][24][25] the onset of the renal phenotype in Sdccag8 gt/gt mice occurred relatively late. The process of cyst formation appeared to coincide with interstitial fibrosis that surrounded the glomeruli and nephrons.…”
Section: Sdccag8 and Degenerative Phenotypesmentioning
confidence: 81%
“…3 Our histologic analysis of the kidneys showed that Sdccag8 gt/gt mice displayed a classic nephronophthisis phenotype at P100, with the cystic dilations originating from the DCTs and CCDs. Compared with other mouse models of nephronophthisis, [22][23][24][25] the onset of the renal phenotype in Sdccag8 gt/gt mice occurred relatively late. The process of cyst formation appeared to coincide with interstitial fibrosis that surrounded the glomeruli and nephrons.…”
Section: Sdccag8 and Degenerative Phenotypesmentioning
confidence: 81%
“…Proteins from homogenized total renal tissue were analyzed by western blotting using antibodies against Caspase-8 (Santa Cruz Biotechnology, Inc., CA) and actin (Cell Signaling Biotechnology, Beverly, MA) as described previously [37]. Three kidneys were used for one experiment group, and data were collected by three independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Additional roles in cardiac morphogenesis, independent of global L-R asymmetry determination, have also been argued (McQuinn et al, 2001). Furthermore, kidneys of Invs inv mutant mice exhibit defects including cyst formation and a delay in tubular maturation (Yokoyama et al, 1993; Sugiyama and Yokoyama, 2006). The early lethality of this mouse mutant detracts from its utility as a model, although it has proven to be an excellent tool.…”
Section: Nephronophthisismentioning
confidence: 99%